(untitled) (Journal of Atomic and Molecular Sciences, 2011)
The two-body Coulomb problem with sources is studied. Closed form solutions are provided for particular non-homogeneities used within the J-matrix method. The results are employed to build analytical solutions having incoming, outgoing and standing wave asymptotic conditions.